If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -8)(4x + 2) = 10x(x + -8) Reorder the terms: (-8 + x)(4x + 2) = 10x(x + -8) Reorder the terms: (-8 + x)(2 + 4x) = 10x(x + -8) Multiply (-8 + x) * (2 + 4x) (-8(2 + 4x) + x(2 + 4x)) = 10x(x + -8) ((2 * -8 + 4x * -8) + x(2 + 4x)) = 10x(x + -8) ((-16 + -32x) + x(2 + 4x)) = 10x(x + -8) (-16 + -32x + (2 * x + 4x * x)) = 10x(x + -8) (-16 + -32x + (2x + 4x2)) = 10x(x + -8) Combine like terms: -32x + 2x = -30x (-16 + -30x + 4x2) = 10x(x + -8) Reorder the terms: -16 + -30x + 4x2 = 10x(-8 + x) -16 + -30x + 4x2 = (-8 * 10x + x * 10x) -16 + -30x + 4x2 = (-80x + 10x2) Solving -16 + -30x + 4x2 = -80x + 10x2 Solving for variable 'x'. Reorder the terms: -16 + -30x + 80x + 4x2 + -10x2 = -80x + 10x2 + 80x + -10x2 Combine like terms: -30x + 80x = 50x -16 + 50x + 4x2 + -10x2 = -80x + 10x2 + 80x + -10x2 Combine like terms: 4x2 + -10x2 = -6x2 -16 + 50x + -6x2 = -80x + 10x2 + 80x + -10x2 Reorder the terms: -16 + 50x + -6x2 = -80x + 80x + 10x2 + -10x2 Combine like terms: -80x + 80x = 0 -16 + 50x + -6x2 = 0 + 10x2 + -10x2 -16 + 50x + -6x2 = 10x2 + -10x2 Combine like terms: 10x2 + -10x2 = 0 -16 + 50x + -6x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-8 + 25x + -3x2) = 0 Factor a trinomial. 2((-8 + x)(1 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-8 + x)' equal to zero and attempt to solve: Simplifying -8 + x = 0 Solving -8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + x = 0 + 8 x = 0 + 8 Combine like terms: 0 + 8 = 8 x = 8 Simplifying x = 8Subproblem 2
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Solution
x = {8, 0.3333333333}
| 3.69+49=13.6161+7x | | 7v=-350 | | -37-8x=-11x+14 | | 9=3(t+14) | | 7x+16=2x | | 13=-4 | | 8=4(y-18) | | -7x-8=8 | | 5b=-10+6b | | 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 | | x^2+px-9=(x-1)(x+q) | | -5t+12t+9t=-16 | | 8v(8v)= | | 2x^2+10x+30= | | 3f-8=6f+10 | | 28=2(-6+x) | | 5x+mk=7k | | 2(2x+3)-4=2x+5 | | -2(r+7)=14 | | 2x^2+12x+30= | | 4+4s=-8 | | -12/s=4 | | 2+(15)x=-7 | | 7-5x=10-(6x-7) | | 4x(x-12)=20 |